EMPLOYEE PERFORMANCE ANALYSIS AT PT PLN (PERSERO) TRANSMISSION SERVICE AND SUBSTATION UNIT (ULTG) PADANG SIDEMPUAN - Lisbeth Lasmaria Cristin Sitohang; Audia Junita; Maksum Syahri Lubis (Universitas KH. Abdul Chalim Mojokerto, 2026)
Employee performance plays a strategic role in supporting organizational operational success, particularly in the electricity sector, which requires reliability, accuracy, and continuity of service. The Transmission Service and Substation Unit (ULTG) Padang Sidempuan, as part of PT PLN (Persero), is responsible for managing transmission networks and operating substations to ensure the stability of electricity supply. This study aims to analyze employee performance and identify the factors that hinder employee performance at PT PLN (Persero) ULTG Padang Sidempuan. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The research informants consisted of the ULTG manager, team leaders, and technical operational employees. The results indicate that employee performance has generally been running fairly well; however, several constraints were identified, including suboptimal work motivation, inconsistent work discipline, and limited equity in training and competency development. This study concludes that improving employee performance requires management support through the fulfillment of work-related needs, strengthening of reward and supervision systems, and continuous competency development in order to enhance operational effectiveness and the quality of electricity services.